2014
DOI: 10.1371/journal.pone.0107451
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoking in HIV-Infected versus General Population in France: Heterogeneity across the Various Groups of People Living with HIV

Abstract: BackgroundAlthough the various groups of people living with HIV (PLWHIV) considerably differ regarding socioeconomic and behavioral characteristics, their specificities regarding tobacco smoking have been poorly investigated. We aimed to assess patterns of tobacco consumption across the various groups of PLWHIV and to compare them to the general population, accounting for the specific socioeconomic profile of PLWHIV.MethodsWe used data of the ANRS-Vespa2 study, a national representative survey on PLWHIV conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
2
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 38 publications
(67 reference statements)
7
41
2
10
Order By: Relevance
“…Two studies used the Fagerström Test for Nicotine Dependence 38 to examine moderate or strong dependence on nicotine in PLWH by gender 39,40 , a third study used the Modified Fagerström Tolerance Questionnaire 41 , and a fourth study defined dependence by either the time to first cigarette in the morning (<30 minutes) or CPD (>20) 42 . While there was no significant gender difference in the report of moderate/strong nicotine dependence in 509 adults in France (men 60.9%; women 58.2%; OR=1.12, 95% CI=0.61-2.06) 39 , a lower percentage of women (47.8%) than men (60.0%) reported moderate/strong nicotine dependence in a sample of 1094 U.S. adults (OR=1.5, 95% CI=1.0-2.2, p<0.05) 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies used the Fagerström Test for Nicotine Dependence 38 to examine moderate or strong dependence on nicotine in PLWH by gender 39,40 , a third study used the Modified Fagerström Tolerance Questionnaire 41 , and a fourth study defined dependence by either the time to first cigarette in the morning (<30 minutes) or CPD (>20) 42 . While there was no significant gender difference in the report of moderate/strong nicotine dependence in 509 adults in France (men 60.9%; women 58.2%; OR=1.12, 95% CI=0.61-2.06) 39 , a lower percentage of women (47.8%) than men (60.0%) reported moderate/strong nicotine dependence in a sample of 1094 U.S. adults (OR=1.5, 95% CI=1.0-2.2, p<0.05) 40 .…”
Section: Resultsmentioning
confidence: 99%
“…The ANRS-Vespa study [VIH, enquête sur les personnes atteintes—HIV, survey on people living with HIV] was a repeated cross-sectional survey conducted among two large, nationally representative samples of HIV-infected people followed at hospitals in France in 2003 and 2011, with the primary aim of assessing the various dimensions of the socioeconomic conditions and health of PlwHIV in France. Full details regarding the study design are available elsewhere[22,23]. …”
Section: Methodsmentioning
confidence: 99%
“…The ANRS-Vespa2 survey was conducted between April 2011 and January 2012 among 3022 PlwHIV recruited in 73 hospital departments in mainland France, using a similar design. In both surveys and each participating hospital department, a sample of eligible patients (5080 in 2003 and 5617 in 2011), randomly selected according to the order of their appointment, were invited to participate by their physician[22]. In the ANRS-Vespa1 and ANRS-Vespa2 studies, after having being informed of the survey by their physician, eligible patients who agreed to participate signed a letter of informed consent in duplicate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have showed that PLWHA lose more life years to smoking than to HIV. 22,23 We must not view lung cancer screening as an alternative to smoke cessation. 24 Although beyond the scope of this review, the British HIV Association has recently published a comprehensive review of how best to address smoking cessation efforts in PLWHA.…”
Section: Lung Cancermentioning
confidence: 99%